Efeito da deriva simulada de glyphosate em diferentes partes da planta de Eucalyptus grandis - Peres Rodrigues da Costa, Andreia Cristina; da Costa, Neumarcio Vilanova; Rocha Pereira, Maria Renata [UNESP]; Martins, Dagoberto [UNESP] (Universidade Estadual de Londrina (UEL), 2012)
The present work aimed to evaluate the effects of simulated drift of glyphoste on Eucalyptus grandis, through the application of low doses in different parts of the plant. The experimental design was a randomized block design with five replications. The treatments were glyphosate application at 0; 30; 60; 90 e 120 g a.e. ha(-1) of the commercial formulation Scout (R). Three forms of application were used: applying on leaf, on stem, and on the entire plant (leaf + stem). For leaf application, stems were covered with plastic ribbons to protect them from the solution; the same was made with plants that were sprayed on stems, covering leaf with plastic bag. The application was carried out in an armed stationary spray tips XR 11002 VS, with 183 KPa pressure in volume of 200 L ha(-1). The eucalyptus plants receiving applications in leaves and whole plant (leaves + stem) showing effects of intoxication are more intense about the plants that received the stem applications only. However, there may be increases in height growth and total dry mass of eucalyptus plants in applications of 30 g a.e. ha(-1) glyphosate.
Simulated drift effect of glyphosate in different parts of Eucalyptus grandis plants
Keywords: Eucalyptus; herbicide; simulated drift